Empowerment Public Based Nationality: Strengthening Indonesian National Values in Coastal Communities in Malaysia - Mustaid; Oman Hadiana; Tio Heriana; Hana Astria Nur; Rifqi Ahmad Fauzi (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
This community service located on the Deep Coast of Kuala Lumpur Malaysia aims to provide education about nationality. The aim of taking nationality is because it is very strategic with the problems explained in the discussion and also seeing the large number of Indonesians who are on the Inner Coast of Kuala Lumpur, Malaysia. The method used is several stages which are carried out according to the procedure. Based on the problems obtained, the author created the title